Analysis of the Inactive Archive Storage System at PT Supra Nusa Kencana - Stephanie Marsha Sabila; Chirstian Wiradendi Wolor; Marsofiyati (Formosa Journal of Applied Sciences, 2023)
Archive storage systems are divided into two, namely active and inactive archive storage systems. This research was conducted in order to find out how good archive management is assessed from the archive storage system, especially in the inactive archive storage system. This research was conducted using a descriptive qualitative approach, with data collection techniques in the form of observation, interviews, documentation and article searches, as well as using purposive sampling. The research location is Jalan Baung Raya, Kebagusan, Pasar Minggu, South Jakarta. The archive management system at PT Supra Nusa Kencana is running well, focusing management on four stages, namely structuring archives, borrowing archives, maintaining archives, and destroying archives. The inactive archive storage system is also working well.